2019
DOI: 10.48550/arxiv.1910.11207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Higher regulators of Siegel varieties

Abstract: We construct classes in the middle degree motivic cohomology of the Siegel variety of almost any dimension. We compute their image by Beilinson's higher regulator in terms of Rankin-Selberg type automorphic integrals. In the case of GSp( 6), using results of Pollack and Shah, we relate the integral to a non-critical special value of a degree 8 spin L-function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…For the group GSp 4 and the classes constructed in [LSZ19], recent progress on this has been announced by Loeffler and Zerbes. In [CLRJ19], we have shown that our motivic classes (in the case of trivial coefficients) are related to non-critical special values of the complex spin L-function, as predicted by the conjectures of Beilinson and Bloch-Kato, through Deligne's regulator taking values in Deligne cohomology. This gives a link between the special values of the arithmetic p-adic spin L-function at certain integers and non-critical special values of of the spin L-function.…”
Section: A Proof Of Lemma 34mentioning
confidence: 61%
See 3 more Smart Citations
“…For the group GSp 4 and the classes constructed in [LSZ19], recent progress on this has been announced by Loeffler and Zerbes. In [CLRJ19], we have shown that our motivic classes (in the case of trivial coefficients) are related to non-critical special values of the complex spin L-function, as predicted by the conjectures of Beilinson and Bloch-Kato, through Deligne's regulator taking values in Deligne cohomology. This gives a link between the special values of the arithmetic p-adic spin L-function at certain integers and non-critical special values of of the spin L-function.…”
Section: A Proof Of Lemma 34mentioning
confidence: 61%
“…We expect an explicit reciprocity law to hold, relating values of Bloch-Kato's dual exponential maps of our Iwasawa class to certain values of the complex spin L-function, which should also show the non-vanishing of the classes. Progress in this direction has been achieved in [CLRJ19], where the archimedean regulator of the motivic classes (for trivial coefficients) has been calculated in terms of the complex spin L-function at noncritical points, using techniques in [Kin98], [Lem17] and [PS18]. This establishes a connection between the arithmetic p-adic spin L-function constructed in this article with the complex spin L-function, in the spirit of Perrin-Riou conjectures.…”
Section: Final Remarks and Future Workmentioning
confidence: 96%
See 2 more Smart Citations
“…In particular, the previously-known techniques are not sufficient to prove an explicit reciprocity law for the Euler system constructed in [LSZ17] for automorphic representations of GSp 4 ; this is the major obstacle that must be solved in order to use this new Euler system to prove the Bloch-Kato conjecture for automorphic motives attached to this group. The same difficulty arises for several other recently-discovered Euler systems, such as those of [LLZ18,CLRJ19,LSZ19].…”
mentioning
confidence: 92%